2014
DOI: 10.3390/microorganisms2010011
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Ecological Understanding of Dinoflagellate Cyst Functions

Abstract: The life cycle of many dinoflagellates includes at least one nonflagellated benthic stage (cyst). In the literature, the different types of dinoflagellate cysts are mainly defined based on morphological (number and type of layers in the cell wall) and functional (long- or short-term endurance) differences. These characteristics were initially thought to clearly distinguish pellicle (thin-walled) cysts from resting (double-walled) dinoflagellate cysts. The former were considered short-term (temporal) and the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
181
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(185 citation statements)
references
References 99 publications
3
181
1
Order By: Relevance
“…motility, morphology and cell division) was also observed in cultures in 13ºC by day 10. Previous studies have shown that in some species, temporary cysts are capable of division forming socalled division cysts (Bravo & Figueroa, 2014) but these were not actually observed in this study and possible explanations are still unclear. We also observed that a temperature regime of 30°C induced pellicle formation, indicating that temperature stress (both low and high) can cause transformation but with different effects on cell viability and integrity.…”
Section: Discussioncontrasting
confidence: 78%
“…motility, morphology and cell division) was also observed in cultures in 13ºC by day 10. Previous studies have shown that in some species, temporary cysts are capable of division forming socalled division cysts (Bravo & Figueroa, 2014) but these were not actually observed in this study and possible explanations are still unclear. We also observed that a temperature regime of 30°C induced pellicle formation, indicating that temperature stress (both low and high) can cause transformation but with different effects on cell viability and integrity.…”
Section: Discussioncontrasting
confidence: 78%
“…Earlier microscopy (Lovejoy et al, 1993;Okolodkov and Dodgeb, 1996;Jiang et al, 2013) and clone library studies using longer 18S rRNA sequences (Bachy et al, 2011;Lovejoy and Potvin, 2011) have also highlighted the differences between SCM and surface communities over the Arctic. Within the two water masses, communities separated by template suggests a pool of historic DNA, which could include dormant or less active stages, e.g., cysts (Verni and Rosati, 2011;Bravo and Figueroa, 2014), advected non-active species (Lovejoy and Potvin, 2011), preserved free DNA, or non-living material in marine snow (Nielsen et al, 2007;Boere et al, 2011). All of these sources can be transported by currents and persist over long distances (Heiskanen, 1993;Brocks and Banfield, 2009).…”
Section: Interpretation Of Dna and Rna-derived Abundances And Diversitymentioning
confidence: 99%
“…Cyst dormancy is an important stage in the life cycle of dinoflagellates and determines bloom seasonality. However, the relationship between this endogenous (genetic) clock and seasonality is not well understood (Bravo and Figueroa, 2014). Motile dinoflagellates and even temporary cysts are often quickly degraded by bacterial action after death.…”
Section: Introductionmentioning
confidence: 99%